Pengaruh Penambahan Konsentrasi Ekstrak Perasan Lemon (Citrus limon (L.) Terhadap Aktivitas Antioksidan Pada Minuman Teh Bunga Telang (Clitoria ternatea L.) - Priamsari, Margareta Retno; Subarjo, Nonik Triliana Warianti; Yudhantara, Sandi Mahesa (Jurnal Farmasi & Sains Indonesia, 2024)
Herbal tea is a drink made from leaves or flowers that are processed or processed as is done when making tea. A plant that is useful as herbal tea is the butterfly pea flowers (Clitoria ternatea L). Butterfly pea flowers are a safe and natural source of antioxidants. Lemon fruit (Citrus limon (L.) is another plant that is useful as an antioxidant besides butterfly pea flowers. The high nutritional content of lemon fruit, including vitamin C as an antioxidant. Antioxidants are important substances for  the body to maintain human health. This study aims to determine the effect of adding lemon juice extract concentration on antioxidant activity in butterfly pea flower tea drinks. Butterfly pea flower tea is made by brewing at a temperature of 70⁰C for 5 minutes. Lemon juice is made by squeezing using a lemon squeezer. The concentrations used in lemon juice are 25, 50, 100, 200, and 400 ppm. Testing was carried out using the DPPH (1,1-diphenyl-2-picrylhydrazyl) method and the antioxidant potential was seen from the percentage inhibition value and IC50 using UV-Vis spectrophotometric absorbance measurements. The results in this study were obtained using a linear regression equation. Lemon juice extract on butterfly pea flower tea has an IC50 value of 60.792 ppm, while the value IC50 vitamin C is 3,160 ppm. Lemon juice extract on butterfly pea flower tea is classified as a strong antioxidant. This shows that the addition of lemon juice extract to butterfly pea flower tea has an effect on antioxidant activity. The SPSS results of antioxidant activity in butterfly pea flower tea with the addition of lemon juice extract showed a significant difference with the antioxidant activity of vitamin C namely 0,001 (p<0,05).